(untitled) (Archives of Mechanics - Test, 2004)
This article presents the foundations of Newton-Euler rigid body dynamics and its generalized forms in the light of the objectivity principle. We prove that most of the features of dynamics may be directly deduced from this principle and from properties of the group defining the geometry. In particular, these deductions seem to close the conjectures about the relevance of the objectivity principle to dynamics.